2022
DOI: 10.1111/os.13237
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Posterior Percutaneous Endoscopic Unilateral Laminotomy with Bilateral Decompression for Symptomatic Cervical Spondylotic Myelopathy

Abstract: Objective To compare the clinical efficacy of posterior percutaneous endoscopic unilateral laminotomy (PPEUL) and anterior cervical decompression and fusion (ACDF) in the treatment of single‐segment spondylotic myelopathy (CSM). Methods This is a retrospective research, from January 2017 to December 2019, 30 cases were included in the PPEUL group and 32 cases were included in the ACDF group. The operative duration, blood loss, length of stay, complications, Japanese Orthopaedic Association (JOA) score, visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Complications of cervical endoscopy vary depending on the choice of access and commonly include transient neurologic deficits, dural tears, visceral injuries, dysphagia, hematoma, and hoarseness 28–31 . In anterior cervical endoscopy, dysphagia is the most reported, while visceral injuries occur mainly in the esophagus 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Complications of cervical endoscopy vary depending on the choice of access and commonly include transient neurologic deficits, dural tears, visceral injuries, dysphagia, hematoma, and hoarseness 28–31 . In anterior cervical endoscopy, dysphagia is the most reported, while visceral injuries occur mainly in the esophagus 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the other study found that at postoperative final follow-up, VAS scores were 1.57 ± 0.41, and JOA scores were 15.01 ± 1.32. [33] According to the results, the surgeries were completed smoothly without any serious complications such as arterial rupture, dural tear, cerebrospinal fluid leakage, or paralysis. However, one patient with a cervical disc herniation at C4/5 level experienced a decrease in strength in the right trapezius muscle after surgery (from grade 4 preoperatively to grade 3 postoperatively).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the other study found that at postoperative final follow-up, VAS scores were 1.57 ± 0.41, and JOA scores were 15.01 ± 1.32. [33]…”
Section: Discussionmentioning
confidence: 99%
“…The vibration, compression and slight dislocation of the vertebral body will aggravate damage to the spinal cord, which can lead to serious consequences. 30 It is difficult for the assistant to maintain the traction force and position continuously when the traditional S‐hook is used to expose the incision of anterior cervical surgery. The operation inevitably causes vibration and even compression or traction of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%